Soil organic carbon: Associating the Walkley-Black Wet Oxidation Method to Loss on Ignition (Gravimetric method) and Clay Content for Selected Samoan Inceptisols - Anand, Sanjay (European Journal of Applied Sciences, 2022)
Precise estimation of soil organic carbon (SOC) is vital in many scientific fields including natural and applied sciences, as well as climate science researches. Ordinary methods of measuring soil organic carbon (SOC) aren’t sufficient for accurate estimation of C sequestration nor to meet environmental safety standards. Methods that allow for accurate assessment of SOC, which are eco-friendly, and yet practicable are more desirable for use in developing countries. Loss on ignition method (LOI) of appraising SOC offers an alternative method to the traditional Walkley-Black (W-B) method of organic carbon determination. A quantitative relation between LOI and Walkley-Black methods was studied for selected Samoan inceptisols. For this study, 36 soil samples from 0-15 cm depth were collected from 12 sites to determine the levels of SOC (%) by both the methods. Clay contents were also determined and used to develop simple and multiple linear regression equations. Highly significant positive associations (P<0.001) were observed between %OM-WB and %OM-LOI (r = 0.92); %OM-WB and %Clay content (r = 0.91); and, %OM-LOI and %Clay content (r = 0.76). Multiple rectilinear regression equation using clay content of soil and LOI as independent factors and W-B as dependent factor provided reliable estimates of SOC since significant multiple relationship was established (R2 = 0.69, p < 0.001).